Unlocking The Power of Social Media Marketing: A Comprehensive Overview of Universitas Terbuka Sulawesi’s Strategies and Successes - Budiman, Rahmat; Wiradharma, Gunawan; Rahmawati, Dwi; Riady, Yasir (Universitas Medan Area, 2024)
Social media marketing presents its prospects to engage in direct communication with customers, increase brand recognition, increase customer loyalty, and increase sales. Social media platforms offer a wide array of data and analytics that can help brands understand user behavior, tendencies, and needs. Social media allows students to access a wide range of social networking sites at less cost (time and effort) to develop and maintain existing relationships. The practice of social channels of student takeovers is becoming more popular and has increased by 11% since 2017. The purpose of this study was to analyze the activity and content in Instagram social media managed by Universitas Terbuka regional offices located on Sulawesi Island. Socialbakers' professional social media analytics tool is used to monitor the social media activity of selected Instagram accounts and collect data for analysis. The data analyzed includes the content of the selected post and user interaction with the post. Among all Instagram accounts owned by UT in Sulawesi, Makassar has the highest number of followers and vice versa UT Gorontalo has the lowest number of followers, the highest engagement rate is achieved by UT Kendari with an engagement rate of 3.61%. UT Gorontalo creates interactive content on their Instagram page by doing regular Instagram live to interact with their audience, thus allowing the audience to ask questions directly to the host. The landing page was created specifically to receive traffic from campaigns among all UT Sulawesi only UT Majene has attractive images on their landing page